Dampak Penggunaan Media Sosial dalam Degradasi Moralitas Orang Muda Katolik di Paroki Santo Petrus dan Paulus Idanogawo - Evimawati Harefa; Megawati Naibaho; Maniati Gea (Journal New Light, 2025)
This study aims to determine the impact of social media use on the moral degradation of Catholic Youth (OMK). Data validity testing is carried out by triangulation, namely data source triangulation and technique triangulation. The results of this study indicate that the use of social media can have a negative impact on the morality of OMK, such as the spread of hate speech, cyber bullying, and the spread of inappropriate content. However, this study also shows that social media can be used as a means to strengthen the faith and morality of OMK if used wisely and responsibly. This study is expected to contribute to the understanding of the impact of social medicine on the moral degradation of OMK in the Parish of Saints Peter and Paul Idanögawo, and also provide recommendations for the use of social media that can provide something new that is positive for OMK.